2018
DOI: 10.18844/wjet.v10i2.3456
|View full text |Cite
|
Sign up to set email alerts
|

The effect of social network-supported microteaching on teachers self-efficacy and teaching skills

Abstract: The three essential elements of an effective instructional environment are the students, the curriculum and the teacher. The teacher, on the other hand is the glue that combines these items. To train qualified teachers, it is important to use methods that employ theory and practice together in teacher education. In order for microteaching, one of these methods, to be more effective, supporting it with online environments such as social networks may be beneficial. In this respect, this study aims to find out th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 0 publications
1
4
0
1
Order By: Relevance
“…Although she was generally dissatisfied with the peer feedback that she received, Geum Chinsun did also acknowledge that watching her peers’ lessons that also had feedback from the course instructor could give her some helpful ideas for how she could add more varied student practice activities into her lesson. These findings are generally in accordance with those of previous researchers who have also concluded that the activity of microteaching can positively influence learning of new instructional strategies (Kelleci et al, 2018). Likewise, pre-service teachers had positive views of online video microteaching (Saban & Çoklar, 2013) as well as video peer feedback and believed that it helps them to improve their teaching skills (Pham, 2022; Riyanti, 2021; Savas, 2012).…”
Section: Resultssupporting
confidence: 93%
“…Although she was generally dissatisfied with the peer feedback that she received, Geum Chinsun did also acknowledge that watching her peers’ lessons that also had feedback from the course instructor could give her some helpful ideas for how she could add more varied student practice activities into her lesson. These findings are generally in accordance with those of previous researchers who have also concluded that the activity of microteaching can positively influence learning of new instructional strategies (Kelleci et al, 2018). Likewise, pre-service teachers had positive views of online video microteaching (Saban & Çoklar, 2013) as well as video peer feedback and believed that it helps them to improve their teaching skills (Pham, 2022; Riyanti, 2021; Savas, 2012).…”
Section: Resultssupporting
confidence: 93%
“…The teacher, student, and curriculum are the fundamental elements of an effective classroom setting. However, the synergy of these elements basically depends on the technique of the teacher (Kelleci et al, 2018). In theory, the most adopted approach to attaining educational goals is social constructivism, advocated by Vygotsky (1978), who stressed that active learning occurs socially (Gunduz & Hursen, 2015).…”
Section: Theoretical and Conceptual Framework Of The Studymentioning
confidence: 99%
“…Como las escenas de microlearning útiles a la socialización mediática y las identidades lúdicas que lo convierten en multisensorial Hug (2007) y multimodal Dolasinski y Reynolds (2020), adecuado para satisfacer la creciente demanda de desarrollo profesional continuo resultante de los cambios en el lugar de trabajo, donde los procesos tradicionales no son suficientes y las micro metodologías en entornos en línea, como los medios sociales, son eficaces. (Kelleci et al, 2018). Sin embargo, la evaluación ha sido solo un componente de estos procesos, lo que también sucede en entornos donde se usa el papel, y se prefieren pruebas escritas al final del ciclo que no contribuyen al desarrollo de habilidades cognitivas superiores, solo cumplen con la norma Sepúlveda et al (2020), son condiciones que instan a realizar un ejercicio de transposición didáctica en el proceso de evaluación, razón para recurrir a experiencias innovadoras entre las que destaca la evaluación gamificada.…”
Section: Introductionunclassified